2018
DOI: 10.14419/ijet.v7i4.14900
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of features for POS tagging in Kannada

Abstract: This paper proposes a system of part of speech tagging for the South Indian language Kannada using supervised machine learning. POS tagging is an important step in Natural Language Processing and has varied applications such as word sense disambiguation, natural language understanding etc. Based on extensive research into methods used for POS tagging, Conditional Random fields have been chosen as our algorithm. CRFs are used for sequence modeling in POS tagging, named entity recognition and as an alternative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…POS tags are assigned after analyzing each word in the text, authors have demonstrated POS tagging [26] using machine learning algorithms and deep learning algorithms. One of the machine learning algorithms SVM outperforms deep learning techniques with 85% accuracy.…”
Section: Literature Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…POS tags are assigned after analyzing each word in the text, authors have demonstrated POS tagging [26] using machine learning algorithms and deep learning algorithms. One of the machine learning algorithms SVM outperforms deep learning techniques with 85% accuracy.…”
Section: Literature Surveymentioning
confidence: 99%
“… Pass the tokens to a POS tagger developed using the CRF model [25,26]. For the sake of better results, the number of parts of speech is reduced and more generalized, then run the bag of words code into the POS tagger and assign a tag to each word.…”
Section: A Dataset Source and Collectionmentioning
confidence: 99%